ANALISIS PERKEMBANGAN AFEKTIF PESERTA DIDIK MELALUI IMPLEMENTASI TOKEN EKONOMI ”STAR ACHIEVEMENT” PADA PEMBELAJARAN IPAS KELAS V SEKOLAH DASAR - Rizkiyah, Maulida Putri; Muhammad Ma'dinul In'am Al; Ummah, Wildatul; Kamil, Muhammad Ma'dinul In'am Al; Mu'alimin; Usriyah, Lailatul (Universitas Negeri Medan, 2026)
This research was motivated by the low learning enthusiasm of fifth-grade students at MI Darul Ulum in Science and Social Studies (IPAS), which only reached 20%. This passive condition hindered students' affective development and cognitive achievement. The purpose of this study was to analyze the effectiveness of the